A survey of 59 pesticide residues in Turkish chicken eggs using LC-MS/MS. Issue 4 (1st October 2020) - Akgün, Banu; Hamzaoğlu, Mertin; Tosunoğlu, Hakan; Demir, Sema; Deniz, Altan; Zengingönül Gökçay, Remziye
ABSTRACT: An LC-MS/MS multi-residue method was validated for the determination of 59 pesticide residue levels in a chicken egg by using QuEChERS extraction method. The validation parameters used were taken from the SANTE/11813/2017 guideline. The calibration curves for each target pesticide had a good linearity in a range of 1.0 or 2.5 to 100.0 µg kg −1 (r 2  ≥ 0.995). Ten per cent of the total pesticides had LOQ values less than 5.0 µg kg −1 or LOQ values from 5.0 to 10.0 µg kg −1 . The LOQ values were below the MRLs set by the European Commision (EC). Average recoveries (70–120%) and relative standard deviations (RSDs≤20%) were achieved for 59 selected pesticides at different concentrations (5 or 10 and 200 µg kg −1 ). All expanded measurement uncertainties were lower than 50%. The occurrence of these pesticides was evaluated in 35 commercially available chicken eggs. No MRL exceedance was identified.